Loneliness and mental health among the elderly in Poland during the COVID-19 pandemic - Beata Dziedzic; Anna Idzik; Ewa Kobos; Zofia Sienkiewicz; Tomasz Kryczka; Wiesław Fidecki; Mariusz Wysokiński (BMC, 2021)
Abstract Background The unexpected changes caused by the COVID-19 pandemic related to the fear of developing the disease, and the need for social distancing and isolation have had an effect on people's mental health. These drastic changes can result in the development of anxiety, depressive symptoms and sense of loneliness. Elderly and chronically ill individuals are at a particularly high risk of developing COVID-19, suffering severe illness and dying as a result of it. Aim of the study The aim of the study was to assess the prevalence of anxiety, depressive symptoms, irritability and loneliness in the elderly aged 60 years and older as a group exposed to the negative impact of the COVID-19 pandemic, and to analyze the relationships between loneliness and mental health of the respondents and sociodemographic variables and chronic diseases. Materials and methods The study was conducted in Poland among 221 individuals aged 60+. The study material was collected using a sociodemographic questionnaire, Hospital Anxiety and Depression Scale (HADS-M) and a revised University of California Los Angeles loneliness scale (R-UCLA). Women accounted for 47.51% and men for 52.49% of study participants; the mean age was 65.18 (SD = 4.06). Results In total, according to HADS-M, depressive symptoms were present in 19.15% of the participants and borderline states in 14.18% of them. Based on R-UCLA, moderate and moderately high sense of loneliness was present in 58.83% of the participants. Sense of loneliness was significantly correlated with the prevalence of depressive symptoms (p < 0.001). Conclusions In this study, one in five participants experienced anxiety and depressive symptoms. Two out of three participants experienced a moderate sense of loneliness. Individuals who displayed a higher level of loneliness also had a higher severity of anxiety level depressive symptoms and irritability. Elderly individuals should be under special care due to their high risk of experiencing physical and mental effects of the COVID-19 pandemic.